Growth Hormone Improves Cognitive Function After Experimental Stroke. Issue 5 (May 2018) - Ong, Lin Kooi; Chow, Wei Zhen; TeBay, Clifford; Kluge, Murielle; Pietrogrande, Giovanni; Zalewska, Katarzyna; Crock, Patricia; Åberg, N. David; Bivard, Andrew; Johnson, Sarah J.; Walker, Frederick R.; Nilsson, Michael; et al.
Abstract : Background and Purpose—: Cognitive impairment is a common outcome for stroke survivors. Growth hormone (GH) could represent a potential therapeutic option as this peptide hormone has been shown to improve cognition in various clinical conditions. In this study, we evaluated the effects of peripheral administration of GH at 48 hours poststroke for 28 days on cognitive function and the underlying mechanisms. Methods—: Experimental stroke was induced by photothrombotic occlusion in young adult mice. We assessed the associative memory cognitive domain using mouse touchscreen platform for paired-associate learning task. We also evaluated neural tissue loss, neurotrophic factors, and markers of neuroplasticity and cerebrovascular remodeling using biochemical and histology analyses. Results—: Our results show that GH-treated stroked mice made a significant improvement on the paired-associate learning task relative to non–GH-treated mice at the end of the study. Furthermore, we observed reduction of neural tissue loss in GH-treated stroked mice. We identified that GH treatment resulted in significantly higher levels of neurotrophic factors (IGF-1 [insulin-like growth factor-1] and VEGF [vascular endothelial growth factor]) in both the circulatory and peri-infarct regions. GH treatment in stroked mice not only promoted protein levels and density of presynaptic marker (SYN-1 [synapsin-1]) and marker of myelination (MBP [myelin basic protein]) but also increased the density and area coverage of 2 major vasculature markers (CD31 and collagen-IV), within the peri-infarct region. Conclusions—: These findings provide compelling preclinical evidence for the usage of GH as a potential therapeutic tool in the recovery phase of patients after stroke. Abstract : Supplemental Digital Content is available in the text.